Antimicrobial mechanisms of nanopatterned surfaces—a developing story - Pirouz, Arash; Papakonstantinou, Ioannis; Michalska, Martyna (Frontiers in Chemistry, 2024)
Whilst it is now well recognized that some natural surfaces such as seemingly fragile insect wings possess extraordinary antimicrobial properties, a quest to engineer similar nanopatterned surfaces (NPSs) is ongoing. The stake is high as biofouling impacts critical infrastructure leading to massive social and economic burden with an antimicrobial resistance (AMR) issue at the forefront. AMR is one of the most imminent health challenges the world is facing today. Here, in the effort to find more sustainable solutions, the NPSs are proposed as highly promising technology as their antimicrobial activity arises from the topographical features, which could be realized on multiple material surfaces. To fully exploit these potentials however, it is crucial to mechanistically understand the underlying killing pathways. Thus far, several mechanisms have been proposed, yet they all have one thing in common. The antimicrobial process is initiated with bacteria contacting nanopatterns, which then imposes mechanical stress onto bacterial cell wall. Hence, the activity is called “mechano-bactericidal”. From this point on, however, the suggested mechanisms start to diverge partly due to our limited understanding of force interactions at the interface. The aim of this mini review is to analyze the state-of-the-art in proposed killing mechanisms by categorizing them based on the characteristics of their driving force. We also highlight the current gaps and possible future directions in investigating the mechanisms, particularly by shifting towards quantification of forces at play and more elaborated biochemical assays, which can aid validating the current hypotheses.